French public attitudes towards the prospect of war in 1938-1939: `pacifism' or `war anxiety'? - Hucker, Daniel (Oxford University Press, 2007)
This article challenges the received wisdom that French public opinion was infused with pacifist sentiment during the 1930s, and that this sentiment in turn contributed to the French defeat of 1940. It will suggest that French public attitudes towards the prospect of war can be better defined as ‘war anxiety’ rather than the value-laden term ‘pacifist’. Taking as a test case the period between the Munich Agreement of September 1938 and the outbreak of the Second World War less than a year later, the article will tease out the necessary distinction between ‘pacifism’ and ‘war anxiety’. By employing a notion of ‘representations’ of public opinion, it will be shown how French opinion was demonstrably less pacifist than many existing analyses assume. Instead, it will be contended that the public’s anxieties with regard to a future war manifested themselves in a variety of ways, of which pacifism was merely one marginal example. Indeed, ‘war anxiety’ increasingly demanded that France prepare for an inevitable conflict, in stark contrast to simply retreating into a defeatist mindset and thus establishing the conditions for the defeat in 1940.